A C3HC4‐type RING finger protein regulates rhizobial infection and nodule organogenesis in Lotus japonicus. Issue 9 (6th September 2018) - Cai, Kai; Yin, Jun; Chao, Hongmin; Ren, Yaping; Jin, Liping; Cao, Yangrong; Duanmu, Deqiang; Zhang, Zhongming
Abstract: During the establishment of rhizobia‐legume symbiosis, the cytokinin receptor LHK1 (Lotus Histidine Kinase 1) is essential for nodule formation. However, the mechanism by which cytokinin signaling regulates symbiosis remains largely unknown. In this study, an LHK1‐interacting protein, LjCZF1, was identified and further characterized. LjCZF1 is a C3HC4‐type RING finger protein that is highly conserved in plants. LjCZF1 specifically interacted with LHK1 in yeast two‐hybrid, in vitro pull‐down and co‐immunoprecipitation assays conducted in tobacco. Phosphomimetic mutation of the potential threonine (T167D) phosphorylation site enhanced the interaction between LjCZF1 and LHK1, whereas phosphorylation mutation (T167A) eliminated this interaction. Transcript abundance of LjCZF1 was up‐regulated significantly after inoculation with rhizobia. The LORE1 insertion mutant and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9‐mediated knockout mutant Lotus japonicus plants demonstrated significantly reduced number of infection threads and nodules. In contrast, plants over‐expressing LjCZF1 exhibited increased numbers of infection threads and nodules. Collectively, these data support the notion that LjCZF1 is a positive regulator of symbiotic nodulation, possibly through interaction with LHK1. Abstract : The plant hormone cytokinin is essential for nodule formation during rhizobia‐legume symbiotic interactions. In this study, a special type of RING protein was found to physically interact with the cytokinin receptor, and involved in fine‐tuning of symbiosis for nodule organogenesis in the model legume Lotus japonicus .